Demographic Characteristics, Anatomical Distribution, and Clinical Presentations of Lipomatosis Tumors Arising from Hand and Wrist - Ergun, Adviye; Akin, Aslan; Sahin, Mehmet Sukru; Kitis, Ali (Journal of Hand and Microsurgery, 2016)
The aim of this study is to analyze demographic characteristics, anatomical distribution, and clinic presentations of the lipomatosis masses in hand and wrist. The hand and wrist magnetic resonance (MR) images of 2,453 patients were evaluated retrospectively. Nineteen cases were included in the study that is seen fat component in mass in MR images. Patients' age, sex, and clinical symptoms were noted. The size and the localization area of the mass were evaluated. Ordinary lipomas were detected in 18 (95%) patients, and fibrolipomatous hamartoma of the median nerve was detected in 1 patient (5%). Benign ordinary lipomas were most frequently observed in palmar and ventral sides. Lipomas located in palmar area tend to be bigger size comparing with other locations. Deep-seated lipoma is localized in central area frequently. In ordinary lipoma cases, patients are generally (78%) asymptomatic. The most frequent clinical symptom is limitation in movement depending on mass dimension.
Keywords: adipose tissue/pathology; diagnosis; differential; hand/pathology; lipoma/pathology; magnetic resonance imaging